2019
DOI: 10.1021/acs.macromol.9b01682
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective and Helix-Sense-Controlled Synthesis of Stereoregular Helical Polycarbenes Using Chiral Palladium(II) Catalysts

Abstract: Living polymerization of diazoacetate monomers bearing an R- or S-methylbenzyl ester (1r or 1s) substituent by a chiral allylPdCl/L R catalyst gives polycarbenes with well-defined molecular weights and low polydispersity. Remarkably, these polymers exhibited unexpectedly high stereoregularity, as revealed by NMR studies. Moreover, the polymerization showed high enantioselectivity on the polymerization of the two enantiomers. The polymerization rate of the two enantiomers can be up to 130 times difference, alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 50 publications
0
24
0
1
Order By: Relevance
“…As shown in Scheme 1, monomer 1 was prepared according to the literature reported previously with slight modifications [38]. After the structures were characterized by 1 H NMR and FT-IR (Figures S1 and S2, Supporting Information (SI)), monomer 1 were polymerized by the complex of π-allylPdCl and Wei-phos (L R ), which was an excellent initiator for polymerization of diazoacetate reported by our group (Scheme 1) [38,39]. Variation on the initial feed ratio of monomer to catalyst produced a range of poly-1 m s with different M n and narrow M w /M n in satisfied yields.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 1, monomer 1 was prepared according to the literature reported previously with slight modifications [38]. After the structures were characterized by 1 H NMR and FT-IR (Figures S1 and S2, Supporting Information (SI)), monomer 1 were polymerized by the complex of π-allylPdCl and Wei-phos (L R ), which was an excellent initiator for polymerization of diazoacetate reported by our group (Scheme 1) [38,39]. Variation on the initial feed ratio of monomer to catalyst produced a range of poly-1 m s with different M n and narrow M w /M n in satisfied yields.…”
Section: Resultsmentioning
confidence: 99%
“…[23] As recently reported by Wu's research group, optically active helical polycarbenes can be obtained using a series of chiral Pd(II) catalysts bearing a rigid phosphine moiety. [24] The helical polycarbenes thus obtained were observed to bear quite stable and hard-to-remove Pd(II)complexes at the end of each chain. Notably, residual metals at the chain ends may have serious negative effects, when polymers are used in the biological and medical fields.…”
Section: Introductionmentioning
confidence: 95%
“…Initially, the living and controlled polymerization of monomers 1a and 1b using 𝜋-allylPdCl chelated with Wei-Phos (L) as initiator was conducted in tetrahydrofuran (THF) at room temperature implementing the procedure described by our group previously. [24,25] Subsequently, the expected polycarbenes were isolated, and, by employing size exclusion chromatography (SEC) (run 1-4, Table S1, Supporting Information), they were determined to exhibit a controlled molecular mass (M n ) and a narrow molecular mass distribution (M w /M n ). The structures of these polycarbenes were characterized by 1 H NMR, 31 P NMR, and Fourier-transform infrared (FT-IR) spectroscopy analyses (Figure 1).…”
Section: Chain-end Functionalization Of Polycarbene With Various Terminal Alkynesmentioning
confidence: 99%
“…De Bruin showed that certain [( N,O ‐ligand)Rh I (diene)] catalysts facilitate the polymerization of ethyl diazoacetate with exquisite stereoregularity and also offer access to high molecular weight derivatives 10 . Toste, Dichtel, and Denmark, and Wu, recently and independently demonstrated that control over the molecular weights of the polymers obtained from the C1 polymerization of alkyl diazoacetates may be achieved through the use of (π‐allyl)palladium dimers as catalysts 6e,8c,11 …”
Section: Introductionmentioning
confidence: 99%